Rates and physicochemical drivers of microbial anabolic activity in deep‐sea sediments and implications for deep time. (27th September 2022) - Meyer, Nicolette R.; Parada, Alma E.; Kapili, Bennett J.; Fortney, Julian L.; Dekas, Anne E.
Abstract: Sediment microorganisms influence global climate and redox by altering rates of organic carbon burial. However, the activity and ecology of benthic microorganisms are poorly characterized, especially in the deep sea. Here, we conducted nearly 300 stable isotope tracer experiments in sediments from the Pacific and Atlantic oceans (100–4500 m water depth) to determine the rates, spatial distribution, and physicochemical controls on microbial total anabolic activity, nitrogen fixation, and inorganic/organic carbon uptake. Using correlative and manipulative approaches, we find that total activity is limited primarily by organic carbon and/or energy. Activity correlates significantly with distance from shore, sediment depth, C:N ratios, and overlying chlorophyll concentrations and is stimulated by carbon but not nitrogen additions. Consistent with this, nitrogen fixation was undetected despite relatively low concentrations of porewater ammonium and the previous detection of nifH genes. Inorganic carbon uptake accounted for 7%–55% of carbon assimilation per sample (median 21%), suggesting chemoautotrophy is an important and unappreciated source of labile carbon in deep‐sea sediments. Community 16S rRNA was dominated by Bacteria (<2% Archaea), primarily Desulfobacterales of the Deltaproteobacteria. Leveraging our findings, we modelled global benthic microbial activity through geologic time and find the potential for significant shifts in total activity with supercontinental cycles.